The role of communication skills in solving the administrative problems among intermediate school leaders in Jeddah - Saad, Tagreed Mohamed (Journal of Economic, Administrative and Legal Sciences, 2019)
The study aimed to identify the role of communication skills among intermediate school leaders in solving administrative problems. The study followed the analytical descriptive method. The questionnaire was used as a data collection tool, and The study sample consisted of (193) educational supervisors in intermediate schools in general education in Jeddah schools. The results showed that the role of communication skills in solving the administrative problems of the leaders of intermediate schools obtained mean of (3.38) and a medium score, And that the communication skills of middle school leaders in the decision-making side had an mean of (3.71) and a high score, The results showed that the role of communication skills among the leaders of intermediate schools in solving the problem of administrative burdens was mean (3.23) and a medium score, And the role of communication skills among intermediate school leaders in solving emergency crises was mean (3.21) and a medium score. The results revealed that there were no statistically significant differences at the level of (α = 0.05) between the mean of the role of communication skills in solving administrative problems among intermediate school leaders and all the factors of the study and the total score according to the variables (scientific qualification, number of years of experience, nature of the current work). The main recommendations of the study were to strengthen the role and importance of the communication skills among school leaders because of their impact on decision-making, solving the problem of administrative burdens, solving emergency crises, conducting training courses in communication skills for school leaders, especially for new leaders; and as one of the terms of reference;. Evaluate the level of communication skills of school leaders from time to time.